A NEW GALACTIC CLUSTER IN PUPPIS - PISMIS, P (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1955)
A previously unrecorded faint galactic cluster at 7h 47m and -25 12 (1900) corresponding to l=214 and b=1, discovered on Schmidt plate of Tonantzintla Observatory is identified.
BOL OBS TONAN TACUB
Keywords: NEW, GALACTIC, CLUSTER, PUPPIS; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; GALAXIAS